ENHANCING READING COMPREHENSION THROUGH COMIC IN VOCATIONAL SCHOOL - Siregar, Rizqia Fitri; Harisma, Rita; Silitonga, Novida Hariana (UIN Sumatera Utara, 2023)
The integral function of reading in fostering scientific literacy is crucial for enhancing pupils' reading proficiency. The utilization of English comics as an instructional medium is anticipated to have a beneficial impact on pupils due to its inherent ability to evoke feelings of happiness among readers. The objective of this study is to enhance the reading comprehension abilities of students in class XI PL SMKN 4 Medan by utilizing English comics as a medium. The present study constitutes a classroom action research that adheres to the research processes outlined in the John Elliot model. These procedures encompass preparation, action, observation, reflection, and evaluation activities. The findings indicated that the mean score for students' reading comprehension fell within the medium range, with a pre-lesson average of 62.70 (57.70%) when utilizing English comic media. Following the acquisition of reading skills and comprehension through the utilization of English entertaining media during the initial phase, there was a noticeable enhancement in the mean reading comprehension proficiency of students, reaching 70 (69.23%). However, it is important to note that this achievement still falls within the moderate range. During the second cycle, there was an observed improvement in students' reading comprehension ability, as evidenced by an increase in the average value and a percentage of 81.54 (88.46%) falling inside the very high group.